Limitations Imposed on Energy Density of Sorption Materials in Seasonal Thermal Storage Systems. (May 2015) - Fumey, Benjamin; Weber, Robert; Gantenbein, Paul; Daguenet-Frick, Xavier; Hughes, Ian; Dorer, Viktor
Abstract: Extensive work is undertaken in search of new materials suitable for thermal sorption storage. High energy capacity is the all sought after goal. In most cases this translates to a high maximum water vapor uptake. While this is notably important, in the system development and operation additional factors become strong contributors to the success or failure of a seasonal thermal storage system. Included are, the required system charging temperature. In domestic applications temperatures below 100 °C are most fitting to the existing building solar collector infrastructure. Further charging limitations can result from possible material characteristics such as crystallization. Just as critical as charging is discharging. It is precisely at this point where much can be gained or lost. In discharging the temperature difference between the minimum absorber temperature and the minimum evaporator temperature is critical. A low temperature difference between these two temperatures permits low resulting sorbent concentrations and thus a high accessible capacity. In a system application, these temperature levels are not freely chosen. These considerations lead to highly varying operation results in both output temperature and concentration. In this paper insight is given in respect to a sorption demonstrator plant based on sodium hydroxide as sorbent and water as sorbate.